Effects of Bitter Bean Extract (Parkia speciosa) on the Histopathological Liver OnWistar Male White Rat (Rattus norvegicus) Which induced by Paracetamol - FAIS ZATUN INDANA AKBAR (HANG TUAH MEDICAL JOURNAL, 2018)
Abstract Background : Paracetamol is an antipyretic analgesic drug, when used in excessive doses or for prolonged periods can cause toxic effects on the liver and may cause cell death or hepatic cell necrosis. Bitter Bean Extract (Parkia speciosa) has a flavonoid compound which is an antioxidant. Objective :This study was aimed to investigate the effect of bitter bean extract (Parkia speciosa) on the histopathology liver on Wistar Male White Rat (Rattus norvegicus) with induced paracetamol. Method: This study was a laboratory experimental study with post-test only control group design using 24 rats divided into 3 groups. Positive control group fed standard feeding diet, aquades and paracetamol 9 mg / day on orally; the treatment group 1 given the Bitter Bean Extract; and group 2 treated with Bitter Bean Extract (Parkia speciosa) 7.2 mg / day with paracetamol 9 mg / day after 45 min . The liver were taken by surgery on the 15th day and microscopically examined. The data were analyzed using IBM SPSS version 23 with KruskalWallis method. Result: Kruskal-Wallis test showed significant result, Mann Whitney test showed that there was a positive influence on treatment 1 and positive control on treatment 2, this can be seen from significance value of p <α (0,05). But there is also a comparison that shows no effect that is on treatment 1 to treatment 2, it is obtained from significance value p> α (0,05). Conclusion: Bitter Bean Extract has affect in reducing liver cell damage which is marked by the necrosis of the hepatic cells in the animals which was given the paracetamol.